Influence of steric effects in solid-phase aza-peptide synthesis. Issue 21 (23rd May 2018) - Arujõe, Meeli; Ploom, Anu; Mastitski, Anton; Järv, Jaak
Graphical abstract: Highlights: Aza-peptide bond formation occurs as typical nucleophilic substitution reaction. Steric and inductive effects influence rate of aza-peptide bond synthesis. Steric hindrance is one reason for the slowness of aza-peptide bond formation. Steric effect was quantified by amino acid graph shape index in aza-peptide synthesis. Maximal coupling time to the aza-peptide was calculated for natural amino acids. Abstract: Aza-peptides are peptide analogs with potential applications as drug candidates. However, due to difficulties associated with the synthesis of these compounds, information regarding their bioactivity is very limited. Herein, we identify steric hindrance as one reason for the slowness of the aza-peptide bond formation reaction. The steric effect of the side group of amino acids in their coupling with the semicarbazide moiety in the synthesis of a model peptide, H-AA-AzAla-Phe-NH2, was studied and quantified using COMU as a coupling reagent. Characterization of the role of this structural factor in aza-peptide bond synthesis is essential for outlining a new and efficient synthesis protocol.